Electronic Theses and Dissertations’ Development in University Libraries in Nigeria - Friday, Jerry Eyerinmene; Afamukoro, Constance Timi-pere (International Journal of Knowledge Content Development & Technology, 2024)
The study was meant to examine electronic theses and dissertations’ development in Nigerian federal university libraries. The study adopted descriptive survey research design. The study population comprised forty-eight institutional repository librarians in eighteen Nigerian federal university libraries. The sample consisted of forty three librarians. A questionnaire was used for data collection. The data collected were analyzed with mean and standard deviation. Findings reveal that the policies available for developing electronic theses and dissertations (ETDs) in the libraries require submission of electronic copies of theses and dissertations by students, participation of digital/IR librarians in ETD development and provision of free access to ETDs; the libraries comply with standards of Open Archives Initiative Protocol for Metadata Harvesting and Search/Retrieval via URL using DSpace for building ETDs and taking advantage of such available ICT facilities as computers, scanners, CD-ROM, LAN, internet connectivity and printer. The libraries achieve ETD through digitisation, mandating submission of electronic versions of TDs by students and creation of IR. However, the process is hindered by technological obsolescence, financial problems, absence of clearly-defined ETD development policy, required ICT facilities and trained staff, copyright, irregular power supply and unstable internet connectivity. This study represents a fresh empirical investigation into electronic theses and dissertations’ development in federal university libraries in Nigeria.